PHOTOCATALYTIC KINETICS OF GASEOUS ACETALDEHYDE DEGRADATION ON LOW INTENSITY ULTRA VIOLET IRRADIATED TiO2 - Sopyan, Iis; Slamet, Slamet; Moedrik, Irwan (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2001)
PHOTOCATALYTIC KINETICS OF GASEOUS ACETALDEHYDE DEGRADATION ON LOW INTENSITY ULTRA VIOLET IRRADIATED TiO2. The kinetics of photocatalytic degradation of gaseous acetaldehyde with semiconductor catalyst TiO2 was studied. The experiment was carried out using TiO2 photocatalyst prepared from titanium tetrachloride (TiCl4) and titanium(lV) isoproxide (Ti(OPr)4) as the starting materials. Comercially available highly active TiO2 from Merck was used for purposes ofcomparison The TiO2 ï¬lms were prepared on soda lime plates and an SiO2-coated soda lime plate using sol-gel method and dip-coating techniques The photocatalytic kinetics of the catalysts were assessed by measuring the photodegradative oxidation of gaseous acetaldehyde at various initial concentrations, UV intensities, and shapes of catalyst. The Merck powder shown the highest photocatalytic activity. All reactions proceeded with approximately first-order reaction kinetics (as indicated from the linear transforms ln(C0/C) as function of irradiation time), especially for the relatively low initial concentration. Meanwhile, at high initial concentration of acetaldehyde, photocatalytic reactions occurred with approximately zero-order kinetics. TiO2 ï¬lm photocatalyst supported on soda lime plate shown lower photocatalytic activity than the powder one, however, when the films were coated on SiO2-coated soda lime plate, photocatalytic activity of the resulting film increased and even higher than that of the powder form.